The Penal Policies Regarding The Implemantation Of The Article Of Adultery In The Penal Code Number 1 Of 2023 - ASYAFFA RIDZQI AMANDHA; Ali Masyhar; Cahya Wulandari (Semarang State University Undergraduate Law and Society Review, 2024)
Penal Code Number. 1 of 2023 revitalizes the adultery article which was previously removed in the old Penal Code. This sparked heated debate about the legal politics behind the criminalization of adultery and its implications for human rights, public morality, and the effectiveness of law enforcement. The criminalization of adultery is based on arguments of morality, family protection, and prevention of other criminal acts. Despite noble intentions, the criminalization of adultery raises concerns about potential invasions of privacy, gender discrimination, and abuse of power. It is important to seek a balance between fair and civilized law enforcement with respect for human rights. Narrow and proportional interpretation, a restorative justice approach, and prevention education are key. This research was carried out by identifying two problems, namely (1) what is the political basis of criminal law for the crime of adultery in the Penal Code Number 1 of 2023, (2) how is the application of the adultery article in the Penal Code Number 1 of 2023. The research method used is juridical research- normative because the subject of the study that will be researched uses library materials as basic material for research by conducting an investigation into the regulations related to the problem being discussed. The results of the research state that the penal policies in the adultery article provide substantive justice based on Pancasila. The implementation of criminalization of adultery is one of the efforts to protect human rights for the family/home through effective and dignified solutions.